Parametric study of the particulate fouling characteristics of vortex generators in a heat exchanger. (25th February 2020) - Han, Zhimin; Xu, Zhiming; Qu, Hongwei
Highlights: An improved Eulerian model containing deposition and removal rates is established. Particulate fouling characteristics in channel with vortex generators is studied. Simulated results of the channel are verified by experimental methods. Effects of height, length, and spacing of the vortex generators are discussed. Abstract: The geometric parameters and flow characteristics of vortex generators have attracted much attention in recent years. For this study, an improved Eulerian method was used to study the fouling characteristics of magnesium oxide nanoparticles in a heat exchanger channel with rectangular wing vortex generators. The fouling characteristics of the channel with and without vortex generators were studied using numerical simulations, with the inlet velocity, magnesium oxide concentration, inlet temperature, and water-bath temperature at 0.5 m/s, 400 mg/L, 298 K, and 318 K, respectively. The simulation results for the rectangular heat channel with and without vortex generators were verified experimentally. Finally, the effects of the vortex generators′ height, length, and spacing on particulate fouling characteristics were evaluated. In comparing the rectangular channel′s fouling characteristics with and without vortex generators, the fouling resistance decreases by 19% for the channel with rectangular vortex generators, and it has the significant advantage of fouling inhibition. Furthermore, the fouling resistance decreases with the increase in the height and length of vortex generators. Conversely, the fouling resistance increases with increased spacing between the vortex generators.